A grid-connected photovoltaic system: mathematical modeling using MATLAB/Simulink - Argyrou, Maria C.; Christodoulides, Paul; Marouchos, Christos; Kalogirou, Soteris A. (My University, 2017)
Renewable Energy Sources, especially solar energy, are important in mitigating environmental problems. Following, a step-by-step modeling of a photovoltaic (PV) system that can be connected to the grid through converters is achieved. The proposed mathematical model is implemented in MATLAB/ Simulink. A maximum power point tracking (MPPT) algorithm finds the maximum power for the operation of the PV system during variations of solar irradiance and ambient temperature. The proposed model is ready to be used for the implementation of energy storage that can provide power and voltage smoothing, peak shaving and standby generation in case of a grid fault.
Keywords: Average model; Grid; Maximum power point tracking; Modeling; P&O algorithm; Photovoltaic; Renewable energy; Simulink